The Students Perception on The Service Quality of Primary Teacher Education (PGSD) in Faculty of Teacher Training And Education (FKIP) of Tanjungpura University (UNTAN) - Suhardi Marli (Universitas Tanjungpura, 2019)
The problem in this study was